PATRIARCHAL CONTROL OVER REPRODUCTIVE HEALTH: LINKS TO MATERNAL MORTALITY AND HOUSEHOLD POVERTY IN RURAL COMMUNITIES IN SOUTHEAST NIGERIA - Chikere, Princewill; Osita-Njoku, Agnes; Umeh, Vincent O. (African Journal of Social and Behavioural Sciences, 2025)
The essence of the study on patriarchal control over reproductive health was to explore the impact of patriarchal control on women’s reproductive health decision-making; the relationship between household poverty and maternal mortality in rural communities with strong patriarchal influence, and the role of cultural and social norms driven by patriarchal values in shaping maternal health-seeking behaviors in Southeast Nigeria. Relevant literature was reviewed as authoritative support for the study, while the Gender and Development (GAD) Theory was adopted as the theoretical framework. Employing a descriptive survey design, a sample of 360 respondents was selected from two communities in each of the five southeast states (Abia, Anambra, Ebonyi, Enugu, and Imo) using multistage and snowball sampling. Data were collected through a structured questionnaire and in-depth interviews, and analyzed using SPSS v.23. Findings revealed a statistically significant relationship between patriarchal control and poor maternal health outcomes. The compounded effect of poverty and patriarchal influence also demonstrated a strong association with maternal mortality. Furthermore, cultural norms rooted in patriarchy were found to delay maternal health-seeking behaviors significantly. The study concluded that patriarchal systems not only restrict women’s access to life-saving maternal healthcare but also perpetuate intergenerational poverty. Recommendations include empowering women through community-based education, subsidizing healthcare for low-income households, culturally adapting health programs, and launching rural economic empowerment initiatives for women.